2020
DOI: 10.1186/s12883-020-01632-4
|View full text |Cite
|
Sign up to set email alerts
|

Choreographing life-experiences of balance control in people with Parkinson’s disease

Abstract: Background: Parkinson's disease (PD) is a devastating neurodegenerative disorder. Reduced balance is one of the cardinal symptoms of PD, predisposing people living with PD to experience difficulties with the execution of tasks and activities, as well as hindering their involvement in meaningful life areas. The overarching aim of this study was to explore how deficits in balance control manifest in everyday life and how it is managed by people with PD (PwPD). Methods: Qualitative description was used as methodo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
1
1
0
Order By: Relevance
“…Previous research has shown that PD in general (i.e., not only PD+FOG) is associated with greater conscious processing of walking movements [33,34]. On this basis, the overall group results presented here may well be similar to visual search behavior in people with PD who do not experience freezing in daily life; particularly if these behaviors are indeed a consequence of and/or required to engage in conscious movement processing (as suggested above).…”
Section: Between Group Differences In Visual Search Gait-specific Conscious Processing and Gait Characteristicssupporting
confidence: 73%
See 1 more Smart Citation
“…Previous research has shown that PD in general (i.e., not only PD+FOG) is associated with greater conscious processing of walking movements [33,34]. On this basis, the overall group results presented here may well be similar to visual search behavior in people with PD who do not experience freezing in daily life; particularly if these behaviors are indeed a consequence of and/or required to engage in conscious movement processing (as suggested above).…”
Section: Between Group Differences In Visual Search Gait-specific Conscious Processing and Gait Characteristicssupporting
confidence: 73%
“…Specifically, people with PD+FOG seem to rely more strongly on visual information to process ongoing stepping movements [12], a control strategy which likely reflects increased conscious processing of movement [12,31,32]. People with PD generally report an increased use of conscious movement strategies to regulate walking movements [33,34], particularly when walking in complex environments necessitating effective visuomotor control [34]. Such conscious movement strategy likely reflects a potentially adaptive mechanism employed to overcome the loss of movement automaticity [35].…”
Section: Parkinson's Disease and Visuo-motor Control During Locomotionmentioning
confidence: 99%